Discussão sobre comunidade e características das comunidades rurais no município de Catalão (GO) - Silva, Juniele Martins; Hespanhol, Rosangela Aparecida De Medeiros (Universidade Federal de Uberlândia, Instituto de Geografia, Programa de Pós-Graduação em Geografia, 2016)
ABSTRACT In studies on community we have mainly two perspectives. To the classic discussions the main focus is the differentiation between community and society; the community is characterized by homogeneity, territorial base and the sense of locality. The contemporaneous perspectives, in turn, advances in the analysis by considering individual differences, besides the territorial basis is not essential criterion for its existence, because is possible to belong to a community even from afar. Considering the changes that the concept of community has undergone and the importance of their understanding at present, this article aims to understand the main discussions on community and the characteristics of rural communities Custódia, Ribeirão, São Domingos and Tambiocó in municipality of Catalão, Goiás. The procedures adopted for the preparation of this article were survey and review of relevant works to the topic and application of interview forms to 75 responsible for the productive units of the selected locations, which represented a percentage of 34.70% of families: 19 (35 18%) in Custódia, 21 (35%) in Ribeirão, 17 (33.33%) in São Domingos and 18 (35.29%) in Tambiocó.

RESUMO Nos estudos sobre comunidade há, principalmente, duas perspectivas. As discussões clássicas consideram como principal foco a diferenciação entre comunidade e sociedade, sendo que a comunidade tem como características a homogeneidade, a base territorial e o sentimento de localidade. Já as perspectivas contemporâneas avançam nas análises ao considerar as diferenças individuais, além da base territorial não ser critério essencial para sua existência, pois é possível pertencer a uma comunidade mesmo à distância. Considerando as mudanças que o conceito de comunidade passaram e a importância do seu entendimento na atualidade, o presente artigo tem como objetivo compreender as principais discussões de comunidade e as características das comunidades rurais Custódia, Ribeirão, São Domingos e Tambiocó, no município de Catalão (GO). Os procedimentos adotados para a elaboração desse artigo foram levantamento e revisão de obras pertinente à temática e aplicação de formulário de entrevista a 75 responsáveis pelas unidades produtivas das localidades selecionadas, o que representou um percentual de 34,70% das famílias, sendo 19 (35,18%) na Custódia, 21 (35%) na Ribeirão, 17 (33,33%) na São Domingos e 18 (35,29%) na Tambiocó.
Discussion on community and characteristics of the rural communities in the municipality of Catalão (GO)
Keywords: Community; Rural communities; Municipality of Catalão (Goiás); Comunidade; Comunidades rurais; Município de Catalão (GO)